[60]Fullerene‐quinoxaline, benzothiadiazole and benzoselenadiazole based dyads for thermally stable polymer solar cells: anchoring of substituent on fullerene with a poly(3‐hexylthiophene) polymer chain. Issue 11 (21st August 2018) - Elavarasan, Kumaravel; Saravanan, Chinnusamy; Panneer Selvam, Nagarajan; Hsieh, Yen‐Ju; Chang, Yi‐Min; Wang, Leeyih
ABSTRACT: [6, 6]‐Phenyl‐C61 ‐butyric acid methyl ester (PC61 BM and PC71 BM) is an archetypal electron acceptor in organic photovoltaic devices. However, it nucleates and grows to form aggregates or crystallites on a length scale of tens of nanometres to micrometres under thermal aging, which often results in a significant decrease in device efficiency and stability. To overcome this thermally induced performance degradation, many methods have been reported to date such as the introduction of hydrogen, halogen bonding, thermally or photochemically crosslinkable groups onto the fullerene, and the suppression of nucleation and growth of fullerene crystallites under thermal aging has been successfully demonstrated. Even though those methods are highly useful for the suppression of aggregation, we successfully demonstrated another one simple method for the same: Introduction of bulkier groups onto the fullerene, which can act as anchoring group to suppress the aggregation. In an extension of our previous work, quinoxaline (TQT), benzothiadiazole (TBTT) and benzoselenadiazole (TBST) based bulkier groups are linked to the fullerene, denoted as TQT‐C60, TBTT‐C60 and TBST‐C60, respectively, through the 1, 3‐dipolar cycloaddition of corresponding azomethine ylides with fullerene. Single junction bulk heterojunction polymer solar cells were fabricated with the configuration ITO/PEDOT:PSS/P3HT:dyad/Ca/Al. The morphological stability of the active layer was monitored by transmission electron microscopy and optical microscopy. Independent of heteroatoms, all the dyads show excellent morphological stability under thermal aging compared to the archetypal acceptor PCBM due to the anchoring of substituent groups. © 2018 Society of Chemical Industry Abstract : To overcome the aggregation of fullerene derivatives in the active layer of organic photovoltaic devices under thermal aging, many techniques have been reported to date such as the introduction of hydrogen bonding, halogen bonding, thermally and photochemically crosslinkable groups onto the fullerene. Here, we successfully demonstrated another one simple technique for the same: Introduction of bulkier group onto the fullerene, which can act as anchoring group to suppress its aggregation